Chapter Using diver-operated stereo-video to monitor juvenile fish assemblages in Mediterranean coastal habitats formed by macrophytes - Disdier-Gomez, José M. (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Littoral systems with macrophytes are nursery areas for fish. We aim to develop a combination of stereo-video and habitat mapping methods for studying fish recruitment at various temporal and spatial scales. Some benefits are: videos are permanent and data can be used for developments of artificial intelligence. There are also disadvantages: cameras have a limited field of view and video processing is time-consuming. Introducing this methodology is of great importance to assess changes in the habitat structure and the ecosystem functions provided for the fish community.